Angiography and the aetiology of heart failure. Issue 838 (August 1995) - Brookes, C. I.; Hart, P.; Keogh, B. E.; Cleland, J. G.
Abstract : The diagnosis of idiopathic dilated cardiomyopathy should not be made without first performing a coronary angiogram. If the cause of heart failure is unknown this should be stated rather than attributing the cause to dilated cardiomyopathy. Severe ventricular dysfunction may improve dramatically after revascularisation in some cases of coronary disease. Preservation of R waves on the surface electrocardiogram suggests the presence of hibernating myocardium but thallium scintigraphy or positron emission tomography scanning should be employed to investigate this further.